Association between Improved Colorectal Screening and Racial Disparities - Doubeni, Chyke A; Corley, Douglas A; Zhao, Wei; Lau, YanKwan; Jensen, Christopher D; Levin, Theodore R (The New England journal of medicine, 2022)
In this study involving non-Hispanic Black members and non-Hispanic White members of the Kaiser Permanente Northern California health plan from 2000 through 2019, colorectal cancer screening increased markedly among both Black members and White members, and racial disparities in colorectal cancer incidence and mortality were virtually eliminated.